Assessing monstrous fan in Malaysia: Present and future - Raja Nor Firdaus Kashfi Raja Othman; Nurfaezah Abdullah; Amiruddin Ahamat; Nor Aishah Md Zuki; Fairul Azhar Abdul Shukor; Kasrul Abdul Karim (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
In the last few years, the monstrous fan has gained attention in this country for large space buildings and areas. The continuity of this product technology is important to allow it to be able to survive in the current and future market. However, there are limited studies on the present and future scenario of the monstrous fan, especially in Malaysia. Thus, the objective of this paper is to forecast its present technology, evaluating the market demand and future of the monstrous fan. For these reasons, an online survey was used to obtain feedback from suppliers and manufacturers to forecast the future of this product. In conclusion, the monstrous fan has been discussed and predicted, which can be beneficial for various parties including policy makers, government, business and technology players by representing a specific knowledge on the technical specificities of monstrous fans in Malaysia.
Keywords: 650; monstrous fan; HVLS; giant fan; large building; forecasting